Long-run effects of lottery wealth on psychological well-being - Erik Lindqvist; Robert Östling; David Cesarini (Research Institute of Industrial Economics (IFN), 2018)
We surveyed a large sample of Swedish lottery players about their psychological well-being and analyzed the data following pre-registered procedures. Relative to matched controls, large-prize winners experience sustained increases in overall life satisfaction that persist for over a decade and show no evidence of dissipating with time. The estimated treatment effects on happiness and mental health are significantly smaller, suggesting that wealth has greater long-run effects on evaluative measures of well-being than on affective ones. Follow-up analyses of domain-specific aspects of life satisfaction clearly implicate financial life satisfaction as an important mediator for the long-run increase in overall life satisfaction.
Keywords: D69; I31; 330; Psychological Well-being; Subjective Well-being; Happiness